Impact of packaging towards consumer buying behavior: case study for ACISB in Rawang / Nurul Syahida Ya'acob - Ya'acob, Nurul Syahida (2006)
The importance of packaging is growing in competitive markets for packaged food products. This research utilized a convenience methodology which is mall intercept personal interview to understand consumer buying behavior towards food products and how packaging elements can affect their buying behavior. Four elements in packaging consisting of graphic design, size and shape, product information and technology will become the focus of this study. The findings highlighting that product information plays a major role in influencing consumers to buy such product. Most respondents say they use label information when they need information regarding the nutritional facts and the ingredients of the product. The challenge for researcher is to integrate packaging into an effective buying decision model, by understanding packaging elements as important marketing communications tools. Future research is proposed and it should be conducted using a bigger sample size and additional element of packaging to see the impact on consumer behavior. Another aspect of consumer behavior other than attitude, motivation, perception and learning also should be identify to better understanding the impact of packaging towards purchasing behavior of the consumer.